The Rowot Sasak Calendar as a Lunisolar System: Ethnoastronomy, Cultural Transformation, and Ecological Sustainability - Muhamad Saleh Sofyan; Arino Bemi Sado; Abd Kohar; Maruf Maruf (Jurnal Dialog, 2026)
The Rowot Sasak Calendar is an indigenous calendrical system that once connected ritual time, agricultural cycles, and ecological knowledge in Lombok. This article examines how Islamization and cultural acculturation gradually shifted the calendar from a lunisolar-stellar system to a predominantly lunar-religious system, thereby weakening its agrarian and seasonal functions. The study aims to explain the calendar’s original astronomical structure, analyze the consequences of removing intercalation, and propose a culturally grounded model for restoring its ecological relevance. Using a qualitative-descriptive approach based on ethnoastronomy and religious-cultural studies, the research was conducted in East Lombok, North Lombok, Central Lombok, and West Lombok in 2025. Data were collected through participatory observation, semi-structured interviews with four key informants, analysis of warige manuscripts and local calendrical records, and comparative astronomical calculations. The findings show that the omission of intercalation caused an annual drift of about 10 to 11 days. Reinstating a thirteenth-month mechanism can restore the calendar’s lunisolar logic while preserving its religious, cultural, and social functions.